Galleria mellonella model identifies highly virulent strains among all major molecular types of Cryptococcus gattii. - Carolina Firacative; Shuyao Duan; Wieland Meyer (PLoS ONE, 2014)
Cryptococcosis is mainly caused by Cryptococcus neoformans. However, the number of cases due to C. gattii is increasing, affecting mainly immunocompetent hosts. C. gattii is divided into four major molecular types, VGI to VGIV, which differ in their host range, epidemiology, antifungal susceptibility and geographic distribution. Besides studies on the Vancouver Island outbreak strains, which showed that the subtype VGIIa is highly virulent compared to the subtype VGIIb, little is known about the virulence of the other major molecular types. To elucidate the virulence potential of the major molecular types of C. gattii, Galleria mellonella larvae were inoculated with ten globally selected strains per molecular type. Survival rates were recorded and known virulence factors were studied. One VGII, one VGIII and one VGIV strain were more virulent (p <0.05) than the highly virulent Vancouver Island outbreak strain VGIIa (CDCR265), 11 (four VGI, two VGII, four VGIII and one VGIV) had similar virulence (p >0.05), 21 (five VGI, five VGII, four VGIII and seven VGIV) were less virulent (p <0.05) while one strain of each molecular type were avirulent. Cell and capsule size of all strains increased markedly during larvae infection (p <0.001). No differences in growth rate at 37°C were observed. Melanin synthesis was directly related with the level of virulence: more virulent strains produced more melanin than less virulent strains (p <0.05). The results indicate that all C. gattii major molecular types exhibit a range of virulence, with some strains having the potential to be more virulent. The study highlights the necessity to further investigate the genetic background of more and less virulent strains in order to recognize critical features, other than the known virulence factors (capsule, melanin and growth at mammalian body temperature), that maybe crucial for the development and progression of cryptococcosis.